Ten years of liquid-phase exfoliation of layered crystals: a bright future ahead? - Backes, Claudia (Chimia, 2019)
Layered materialsare an abundantsource of new nanostructures whenthinneddownto displayfas-cinatinglayernumber-dependentpropertiesdue to quantumconfinementin two dimensions.Aboutten yearsago, it was first demonstratedthat layered crystalscan be exfoliateddownto monolayersin the liquidphasebya relativelysimpleand scalablemethodologytermedliquid-phaseexfoliationthat is widelyapplicableto manystructures. By now, >10 classesof layered materialshave beenmadeaccessibleas two-dimensionalnanosheetsby this technique.In this article,advancementsin exfoliation,size selectionand characterisationare summarised.Remainingchallenges,openquestionsand perspectivesare also discussed